Membangun Entrepreneurship dalam Perspektif Ekonomi Syariah - Yunus Mustaqim (Business Management Analysis Journal (BMAJ), 2019)
Efforts to grow or build entrepreneurship these days are no longer the only thing that need to be done, but it is already a matter that must be or must be done by everyone. This obligation is caused more by an urgent need for someone to get out of economic weakness. This study analyzes about building entrepreneurship in a sharia economic perspective. This research method uses library research with qualitative descriptive data analysis. The results of this study note that building entrepreneurship in the perspective of Islamic economics is to develop a character that is disciplined, independent, realistic, committed, honest, and productive, to realize a benefit that can bring blessings and continue to run its business with attention to the balance of world life and the hereafter. With these characters will have an impact on entrepreneur to always maintain his business well and not to do a business activity that is detrimental to others, such as destroying other people's businesses in a false manner. So that later will reach the goal of life, namely the goal to achieve fallah and maslahah. An entrepreneur thinks of long-term good fortune both the world and the hereafter and does not only look at the material but also looks at the spiritual. Entrepreneur will feel achieved and fulfilled the needs of life in a balanced way between the world and the hereafter.